2009
DOI: 10.3174/ajnr.a1866
|View full text |Cite
|
Sign up to set email alerts
|

Improved Delineation of Ventricular Shunt Catheters Using Fast Steady-State Gradient Recalled-Echo Sequences in a Rapid Brain MR Imaging Protocol in Nonsedated Pediatric Patients

Abstract: BACKGROUND AND PURPOSE: Rapid brain MR imaging is often substituted for head CT in multiply imaged patients with shunted hydrocephalus. Fast TSE-T2 sequences are commonly used in these protocols. One limitation of TSE-T2 sequences is the decreased catheter delineation compared with CT. The aim of this study was to compare fast TSE-T2 with rapid SS-GRE sequences in the evaluation of intracranial shunt catheter delineation as part of a rapid nonsedated pediatric brain MR imaging protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…9,[11][12][13][14][15] A recent study demonstrated value in an 8-second gradient-echo technique for determining ventricular size; however, this technique was performed in cases of failed examinations and provides scarce anatomic detail and, subsequently, minimal additional diagnostic information aside from ventricular size. 16 Despite substantial motion artifacts in some cases, meaningful diagnostic value can be inferred from our results because no cases required conversion to a CT scan or to sedated, standard MR imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[11][12][13][14][15] A recent study demonstrated value in an 8-second gradient-echo technique for determining ventricular size; however, this technique was performed in cases of failed examinations and provides scarce anatomic detail and, subsequently, minimal additional diagnostic information aside from ventricular size. 16 Despite substantial motion artifacts in some cases, meaningful diagnostic value can be inferred from our results because no cases required conversion to a CT scan or to sedated, standard MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Although various techniques have been used, heavily T2-weighted single-shot fast spin-echo and gradient recalled-echo imaging are the 2 most common pulse sequence methods used to interrogate ventricular size and shunt catheter tip location, respectively. 15 Starting in April 2009, our institution introduced a similar T2-weighted HASTE rapid-sequence MR imaging protocol. A significant factor affecting resolution of anatomic detail in MR imaging is patient motion, which is directly related to the time required to complete each sequence.…”
mentioning
confidence: 99%
“…UfMRI has been most commonly used in pediatric neuroradiology for evaluation of intracranial shunts in children with hydrocephalus and majority of reported ufMRI brain protocols include only multiplanar T2-weighted HASTE sequences. [25][26][27][28][29][30][31][32][33][34] Consequently, although an ufMRI has been reported to demonstrate limitations for detection of intracranial hemorrhage, the described ufMRI protocol lacked blood-sensitive sequences. 35 Recently, an ufMRI protocol incorporating sequences in addition to T2 sequences have been reported in pediatric trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 Although subtle parenchymal abnormalities cannot be excluded when using rapid brain MR imaging, the ventricles, cerebral sulci, and basal cisterns can be adequately assessed owing to the good contrast resolution of MR. Visualization of the shunt catheter is not absolutely necessary for assessment of shunt function, though its visualization can be improved by using a gradient-echo sequence. 18 Instituting competitive pricing for rapid brain MR imaging may make it easier to implement the change from head CT to rapid brain MR in assessment of shunted hydrocephalus. At our institution, these 2 studies cost exactly the same amount.…”
Section: Discussionmentioning
confidence: 99%